2016
DOI: 10.1007/s11467-016-0642-x
|View full text |Cite
|
Sign up to set email alerts
|

Floquet control of the gain and loss in a PT-symmetric optical coupler

Abstract: Controlling the balanced gain and loss in a PT -symmetric system is a rather challenging task. Utilizing Floquet theory, we explore the constructive role of periodic modulation in controlling the gain and loss of a PT -symmetric optical coupler. It is found that the gain and loss of the system can be manipulated by applying a periodic modulation. Further, such an original non-Hermitian system can even be modulated into an effective Hermitian system derived by the high-frequency Floquet method. Therefore, compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…time-independent) potentials has been prolific. Recently, manipulation of the spontaneous PT -symmetry breaking (and non-Hermitian physics) by making use of periodic driving schemes has also attracted much attention [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. For example, as shown in references [10,20], the spontaneoussymmetry-breaking phase transition emerges even for arbitrarily weak gain-loss coefficient by adjusting the parameters of periodic driving field.…”
Section: Introductionmentioning
confidence: 99%
“…time-independent) potentials has been prolific. Recently, manipulation of the spontaneous PT -symmetry breaking (and non-Hermitian physics) by making use of periodic driving schemes has also attracted much attention [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. For example, as shown in references [10,20], the spontaneoussymmetry-breaking phase transition emerges even for arbitrarily weak gain-loss coefficient by adjusting the parameters of periodic driving field.…”
Section: Introductionmentioning
confidence: 99%
“…time-independent) potentials. Recently, however, a parallel activity associated with time-dependent PT -symmetric systems has started to attract increasing attention [29][30][31][32][33][34][35][36][37][38][39]. The excitement for this line of research stems from two reasons: the first one is fundamental and it is associated with the expectation that new pathways in the PT -arena can lead to new exciting phenomena.…”
mentioning
confidence: 99%
“…The characteristics of the timeperiodic-driven two-level system with 𝒫𝒯 symmetry were studied and the corresponding phase diagram as a function of the perturbation strength and frequency was obtained. [24][25][26][27][28][29] The time evolution of the two-level system with a timedependent non-Hermitian Hamiltonian without 𝒫𝒯 symmetry was investigated and showed that the system was in general unstable with exponential growth or decay. [30] Recently, the analytical results for the parity-time-symmetric two-level system under synchronous combined modulations was studied.…”
Section: Introductionmentioning
confidence: 99%